The technological contest between China and the United States - Alfredo Toro Hardy (Global Labor Organization (GLO), 2020)
China's proclaimed aim of becoming the world's leader in science, technology and innovation by the mid twenty first century has triggered an intense competition with the United States. The latter, feeling threatened in its supremacy in this field, has reacted forcefully. This GLO Discussion Paper examines the nature of this contest, the comparative technological standing of both countries, the pros and cons in this area derived from their respective development models and the plausible outcomes of this competition.
Keywords: D78; F01; F52; H52; I25; O20; O33; O38; O51; O53; 330; Artificial Intelligence; China; Market economy; Research & Development; Science & Technology; State led model; Silicon Valley; United States